Subject oriented approach to the study of higher spiritual capacities - G V Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2010)
Possibility of using subject oriented approach to the enquiry of spiritual capacities is reviewed; it is suggested holistic consideration of moral and intellectual parameters of subject's spiritual capacities in psychological study of deeds.